Rent-seeking in a unionised monopoly - Straume, Odd Rune (2002)
A unionised monopoly firm, benefitting from some kind of anti-competitive regulation, and its corresponding trade union have a common interest in spending resources to protect the monopoly rents created by the regulation. In the present paper, a situation in which the unionised monopoly is challenged by a consumer organisation fighting for deregulation is analysed as a standard Tullock rent-seeking contest. With unequal sharing of monopoly rents, the free-riding incentives among the rent-defending players turn out to be overwhelming, in the sense that the unique Nash equilibrium is characterised by zero effort contribution by the player with the lower valuation of the contested prize. This implies that being "strong", in terms of bargaining strength, is not necessarily an advantage for neither player in a unionised monopoly that is threatened by deregulation.